KUALITAS PELAYANAN PUBLIK PADA LAYANAN E-TILANG SURABAYA - Fierda Nurany Indriani; Amara Nasya Damayanti; Ferra Aetika Wulandari; Fadillah Nuzul Furqonia; Akhmad Sulthon A.H.K (Faculty of Social and Political Science, 2021)
The purpose of this study is to determine the public service quality of e-traffic ticket in Surabaya. This E-ticket program was issued by District Attorney, due to the large number of complaints from the public regarding the less effective and efficient system. Therefore, the application of e-traffic ticket helps the community (the offender) in paying the fines. It will also facilitate data management of traffic violation cases for the police, the Supreme Court of the Republic of Indonesia, and Attorney General's Office of Indonesia. This study uses a qualitative research method with a descriptive approach. The research data were obtained through interview, observation, documentation, and related triangulation in the administration of e-traffic ticket. The results show that the e- traffic ticket innovation is appropriate, good and profitable for the people in Surabaya, especially people enthusiasm who think positively and agree with this policy, but there are some difficulties experienced by the community due to lack of socialization from the authorities, but the solution is found as by the parties who issued this e-traffic ticket innovation so that the public will not be disappointed.